Social Problems of Margarided Generations: Identity Crisis and The Direction of Youth in The Digital Era - Hasdiansa, Ilma Wulansari (PT Maju Malaqbi Makkarana, 2025)
The study aims to examine the socio-cultural impact of digital on the identity and life orientation of the younger generation. Amid the development of information technology and social media, young people are often faced with social pressure, false standards of success, and loss of authentic values in forming their identity. This phenomenon shows symptoms of an identity crisis that is not only personal, but also systemic as part of a cultural shift. The study highlights how social media shapes self-construction, creates an unhealthy competitive space, and influences important decision-making such as education and career. This crisis shows that the younger generation is in a vulnerable position, both psychologically and socially. This study was conducted using a descriptive qualitative approach, based on in-depth interviews with high school and college students in South Jakarta. The results show that the majority of respondents experience value disorientation, digital self-image pressure, and uncertainty about the direction of life. Research recommendations emphasize the importance of digital literacy, strengthening character education, and developing supportive social spaces to help young people build a healthy identity and a clear direction in life.